Biodiesel Production Optimization from Waste Cooking Oil Using Animal Bone Catalyst - Joy Iruoghene Urete; Michael Owoicho Sule; Juliet Gordon; Olawale Samson Kolade; Roi Nze; Samuel Ayegu Tsebam; Oyedele Babatunde Oyeleye; David Udo Robinson; Ibrahim Ademola Fetuga (The Journal of Engineering and Exact Sciences, 2023)
The goal of the current study is to use a heterogeneous catalyst made from biological-waste (animal bone) to optimize the process parameters needed to transform used cooking oil (WCO) into methyl- esters. The methyl esters and synthetic calcium oxide (CaO) from animal dumps were both analyzed. At temperatures between 900 and 950oC, calcined catalyst was obtained. Utilizing central composite architecture, reaction effects from temperature (40–80oC), time for the reaction (30–180min), as well as CL (1–0.15×102 w/w%) were examined in a 3-level, 3-factor array. To identify the most important parameter, ANOVA testing as well as R.S.M optimization are utilized for the studies. The linear terms of CL (p-value of 0.0146), reaction time (p-value 0.0339), as well as temperature of the reaction combination (p-value of 0.0344) had greatest impact on the biodiesel yield. The quadratic terms of CL (p-value = 0.0271) and temperature of the combining reaction (p-value = 0.0508) had the greatest impact on the oil yield. Therefore, it is practical to apply C.C.D design, R.S.M, as well as ANOVA to optimize the generation of biodiesel from used cooking oil.